What follows after : a novel - Walsh, Dan, 1957- (Revell, a division of Baker Publishing Group, 2014)
In October 1962, Colt Harrison and his little brother, Timmy, hatched a plan. They would run away from their Florida home, head for their aunt's house in Savannah, Georgia, and refuse to come home until their parents got back together. But things go terribly, terribly wrong. Colt's mother and father must come to grips with years of neglect and mistrust in order to recover their beloved sons, their love for one another, and their broken marriage.